1999
DOI: 10.1207/s15327663jcp0803_05
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Numbing: When Lives Are Valued Less as the Lives at Risk Increase

Abstract: Costly life‐saving interventions can often be described not only in terms of the number of lives that may be saved but also in terms of the proportion of lives saved out of some total number at risk. In a phenomenon that has been referred to as psychophysical numbing (PN), Fetherstonhaugh, Slovic, Johnson, and Friedrich (1997) found that participants rated an intervention saving a fixed number of lives to be less worth investing in when more total lives were at risk (i.e., when saved lives represented a smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 26 publications
6
77
0
10
Order By: Relevance
“…This diminishing sensitivity implies that, in perception and decision-making alike, the relationship between objective magnitude and subjective evaluation is often a concave function that is monotonically increasing but marginally decreasing. As we noted earlier, a number of studies have shown that this psychophysical relationship even extends to evaluations of human fatalities: as an event's death toll increases, our sensitivity to the loss of life decreases, so that each additional death has a diminishing affective impact (1,3,4). Other studies have shown a general preference for risky alternatives in decisions under risk involving human losses (2), which also implies a concave disutility function for human fatalities (2,8,9).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…This diminishing sensitivity implies that, in perception and decision-making alike, the relationship between objective magnitude and subjective evaluation is often a concave function that is monotonically increasing but marginally decreasing. As we noted earlier, a number of studies have shown that this psychophysical relationship even extends to evaluations of human fatalities: as an event's death toll increases, our sensitivity to the loss of life decreases, so that each additional death has a diminishing affective impact (1,3,4). Other studies have shown a general preference for risky alternatives in decisions under risk involving human losses (2), which also implies a concave disutility function for human fatalities (2,8,9).…”
mentioning
confidence: 72%
“…Our reactions to these tragic events-including our willingness to provide aid and demand that our governments intervenedepend largely on the extent to which we are moved by the size of their associated death tolls (1). Research in psychology (1)(2)(3)(4) and economics (5)(6)(7) has demonstrated that people tend to show a diminishing sensitivity to the number of human fatalities and, equivalently, a preference for risky (vs. sure) alternatives in decisions under risk involving human losses. As a result, policy makers charged with responding to humanitarian crises or preventing unnecessary deaths may inadvertently fail to maximize the number of lives saved (1).…”
mentioning
confidence: 99%
“…Other research has found a pattern compatible with the identifiable victim effect: people are sensitive to proportions of lives saved rather than absolute values (Baron, 1997;Featherstonhaugh, Slovic, Johnson, & Friedrich, 1997;Friedrich et al, 1999;Jenni & Loewenstein, 1997;Small, Loewenstein, & Slovic, 2007). When the proportion is high, the lives become more identifiable.…”
Section: Vividness: Identifiable Victimsmentioning
confidence: 88%
“…That is, they may improperly factor in the denominator, or reference group, when intuitively calculating the benefit. Indeed, some evidence shows that when primed to think "economically," this bias is even stronger (Friedrich et al, 1999).…”
Section: Vividness: Identifiable Victimsmentioning
confidence: 99%
“…For example, allowing employees to see their customers could lead them to better identify with customers by reducing the perceived social distance (Gino et al 2010, Small andLoewenstein 2005). People tend to be more sensitive to and more highly value a singular life over several lives (Friedrich et al 1999); by extrapolation, seeing actual customers could similarly lead employees to focus on the individual, rather than considering customers as an aggregate, thus increasing the level of care and service. Such research suggests that seeing customers may serve as a source of empowerment for employees, through which they could develop a higher sense of self-efficacy (Conger and Kanungo 1988), prolonged motivation , and greater satisfaction (Hartline andFerrell 1996, Snipes et al 2005).…”
Section: Seeing and Being Seen: Transparency Perceptions And Performentioning
confidence: 99%